HUBUNGAN KINERJA PETUGAS DAN TINGKAT KEPUASAN PASIEN POLI UMUM DI PUSKESMAS TANJUNG KARANG - Rahmi Lestari; Lalu Sulaiman; Sismulyanto Sismulyanto (LPPM Institut Pendidikan Nusantara Global, 2023)
Satisfied patients are a very valuable asset because if patients are satisfied, they will continue to use the services of their choice. Based on data on the number of patient visits to general polyclinics from 2021 there were 11,657 while in 2022 there were 10,013 with an average of 30 patient visits per day. The purpose of this study was to determine the relationship between officer performance and patient satisfaction at the General Polyclinic at the Tanjung Karang Health Center, Mataram City. The research design was